Method for detecting carbon coating uniformity of lithium iron phosphate powder material

Through thermal-differential analysis method, detect the exterior starting point temperature, external push end point temperature and quality increase of the exterior point of the iron phosphate lithium powder material, solve the problem of large detection results in the existing technology, and achieve carbon High accuracy and reliability of cover uniformity detection.

CN119375288APending Publication Date: 2025-01-28WUHU ETC BATTERY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500987.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is used to detect the uniformity of carbon coating of lithium iron phosphate powder materials, which has problems such as large errors in the detection results, low accuracy and cumbersome operation.

Method used

Adopt the heat-weight-differential analysis method. By heating the lithium iron phosphate powder material in the aerobic atmosphere, the proportion of the starting point of the external push, the exterior end point temperature, and the increase of the quality of the external push. sex.

Benefits of technology

This method can significantly distinguish the tiny difference in the degree of lithium carbon in different iron phosphates. The process is simple, the operability is good, the measurement results are stable, the accuracy is high, and the reliability is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119375288A_ABST
    Figure CN119375288A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting the carbon coating uniformity of a lithium iron phosphate powder material, which comprises the following steps: heating the lithium iron phosphate powder material as a sample in an aerobic atmosphere, and respectively measuring the extrapolation initial point temperature, extrapolation final point temperature and mass increase proportion of the sample; and judging the carbon coating uniformity of the lithium iron phosphate powder material according to the relative sizes of the extrapolation initial point temperature, the extrapolation final point temperature and the mass increase proportion of different samples. According to the method, tiny differences of different lithium iron phosphate carbon coating degrees can be obviously distinguished, and the method is simple in process, good in operability, stable in measurement result, high in accuracy and good in reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for detecting the quality of lithium iron phosphate powder material, and in particular to a method for detecting the uniformity of carbon coating of lithium iron phosphate powder material. Background Art

[0002] Although lithium iron phosphate materials have a high theoretical specific capacity and excellent cycle stability, their electronic conductivity is relatively low, which limits their application under high-rate charge and discharge conditions. In order to solve this problem, a carbon source is added during the production and preparation of lithium iron phosphate, and an amorphous conductive carbon coating is generated on the surface while forming the target material. Carbon coating can significantly improve the electronic conductivity between lithium iron phosphate particles, thereby improving the overall conductivity of the material. Moreover, carbon coating can inhibit the continuous growth and agglomeration of lithium iron phosphate particles to a certain extent, thereby obtaining particles with controllable particle size and uniform distribution. In addition, the carbon coating can also serve as a protective layer to prevent lithium iron phosphate particles from being affected by the external environment (such as oxidation, corrosion, etc.) during preparation and use, thereby maintaining the stability of the material and extending its service life.

[0003] At present, scanning electron microscope (SEM) and transmission electron microscope (TEM) are usually used to observe the carbon coating on the surface of lithium iron phosphate to determine the uniformity of the carbon coating of the material. SEM is limited by its resolution and cannot capture the thickness and distribution of the carbon coating of lithium iron phosphate. And when observing, the interpretation of SEM images often depends on the experience and subjective judgment of the observer, resulting in large errors in uniformity judgment. TEM observation requires ultra-thin slice samples, and the preparation process is complicated and time-consuming. And for lithium iron phosphate carbon-coated materials, additional defects or damage may be introduced during the preparation process, affecting the accuracy of the observation results. In addition, the operation of TEM is relatively complicated, requiring professional technicians to operate and maintain, and the equipment cost is also high. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for detecting the uniformity of carbon coating of lithium iron phosphate powder material, so as to solve the problems of large error in detection results, low accuracy and complicated operation in existing detection methods.

[0005] Technical solution: A method for detecting the uniformity of carbon coating of lithium iron phosphate powder material according to the present invention comprises the following steps:

[0006] The lithium iron phosphate powder material is used as a sample and heated in an oxygen atmosphere, and the extrapolated starting temperature, extrapolated end temperature and mass increase ratio of the sample are respectively measured. The uniformity of the carbon coating of the lithium iron phosphate powder material is judged according to the relative sizes of the extrapolated starting temperature, extrapolated end temperature and mass increase ratio of different samples.

[0007] Preferably, the oxygen atmosphere is an air atmosphere, and the heating temperature is no more than 500°C.

[0008] Preferably, the heating temperature is 300-500° C. At this measurement temperature, the carbon coating layer will not react with oxygen, while the lithium iron phosphate not coated by the carbon source will react with oxygen.

[0009] Preferably, the sample comprises at least one lithium iron phosphate powder material standard with a known carbon coating degree and at least one lithium iron phosphate powder material to be tested with an unknown carbon coating degree.

[0010] Preferably, the method for determining the extrapolated starting temperature, extrapolated endpoint temperature and mass increase ratio of the sample is: placing two completely identical crucibles at both ends of the balance of the thermogravimetric-differential thermal instrument, returning the balance to zero, and waiting for the reading to stabilize; filling one of the crucibles with the sample evenly, and filling the other crucible with the reference material; adjusting the DTA signal and returning the differential thermal reading to zero; heating the sample in the crucible to no more than 500°C, analyzing the TG-DTA curve according to the test data, and obtaining the extrapolated starting temperature, extrapolated endpoint temperature and mass increase ratio of the sample.

[0011] The principle of thermal analysis in the present invention is to place the measured substance and the reference substance on a temperature measuring thermocouple under the same conditions, and measure the temperature difference and temperature change and mass change between the two under program temperature control. By recording the temperature change and mass change of the sample during heating, the physical or chemical changes of the sample at different temperatures, such as decomposition, oxidation, reduction, etc., can be inferred.

[0012] In the evaluation of the carbon coating effect of lithium iron phosphate, thermogravimetric analysis can reveal the stability of the carbon coating during the heating process, and whether there is loss or decomposition of carbon materials, thereby evaluating the quality and protective effect of the carbon coating; differential thermal analysis can capture the thermal effects of lithium iron phosphate during the heating process, such as endothermic or exothermic peaks. These thermal effects are closely related to the physical and chemical changes of lithium iron phosphate and carbon coating, such as phase change, chemical reaction, etc.

[0013] Thermogravimetric-differential thermal analysis can directly measure the mass and heat changes of the sample during the heating process, so it can intuitively reflect the quality and thermal stability of the carbon coating, which is not available in some other indirect testing methods (such as electrochemical testing). Thermogravimetric-differential thermal analysis not only focuses on the changes in the carbon coating itself, but also reveals its interaction with the lithium iron phosphate matrix, thereby more comprehensively evaluating the carbon coating effect. Through thermogravimetric-differential thermal analysis, the mass loss and heat change data of the sample at different temperatures can be obtained, which can be used to quantitatively evaluate the quality and thermal stability of the carbon coating.

[0014] Preferably, the method of heating the sample in the crucible is: heating to 500° C. at a heating rate of 5-15° C. / min.

[0015] Preferably, the method of evenly filling the sample into the crucible is: evenly filling 5-15 mg of lithium iron phosphate powder sample without large particle agglomeration into an alumina crucible.

[0016] Preferably, the method for judging the uniformity of carbon coating of lithium iron phosphate powder material according to the relative sizes of the extrapolated starting temperature, extrapolated endpoint temperature and mass increase ratio of different samples is: respectively comparing the extrapolated starting temperature, extrapolated endpoint temperature and mass increase ratio of different samples, and the sample with relatively higher extrapolated starting temperature and extrapolated endpoint temperature and relatively smaller mass increase ratio has higher carbon coating uniformity.

[0017] The principle of judgment is: when there are exposed areas on the surface of lithium iron phosphate that are not coated by carbon, at the above-mentioned measurement temperature, the divalent iron of lithium iron phosphate is oxidized to trivalent iron, and the measured extrapolated starting temperature and extrapolated end temperature are the temperature at the beginning and end of oxidation. The more exposed areas that are not coated by carbon, the easier it is for oxidation to occur, which is manifested as lower extrapolated starting temperature and extrapolated end temperature. At the same time, since oxygen elements will enter lithium iron phosphate through the uncoated areas during oxidation, resulting in an increase in mass, and the carbon coating layer will prevent oxygen elements from entering lithium iron phosphate, the greater the mass increase ratio of the material, the larger the area that is not coated by carbon, the worse the carbon coating uniformity, and vice versa, the better the carbon coating uniformity.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the present invention can significantly distinguish slight differences in the degree of carbon coating of different lithium iron phosphates. The method is not only simple in process and good in operability, but also has stable measurement results, high accuracy and good reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the structural diagram of the thermogravimetric-differential thermal instrument;

[0020] Figure 2 The differential thermal analysis diagram of samples A, B, and C when heated to 500°C in air atmosphere;

[0021] Figure 3 The thermogravimetric analysis diagram of samples A, B, and C when heated to 500°C in air atmosphere;

[0022] Figure 4 The differential thermal analysis diagram of samples A, B, and C when heated to 500°C in a nitrogen atmosphere;

[0023] Figure 5Thermogravimetric analysis of samples A, B, and C when heated to 500°C in a nitrogen atmosphere;

[0024] Figure 6 The thermogravimetric-differential thermal analysis diagram of the carbon source of lithium iron phosphate heated to 800°C in an air atmosphere;

[0025] Figure 7 This is the thermogravimetric-differential thermal analysis diagram of the carbon source of lithium iron phosphate heated to 800°C in a nitrogen atmosphere. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0027] Example 1: The method for detecting the uniformity of carbon coating of lithium iron phosphate powder material is as follows:

[0028] Three lithium iron phosphate powder materials with different carbon coating uniformities were selected and recorded as A, B, and C, where the carbon coating uniformity was: C>B>A, and the carbon coating uniformity of the three materials was greater than 99%.

[0029] The specific surface areas of the three lithium iron phosphates were measured using an SSA-4300 pore size specific surface area analyzer. The results are as follows:

[0030] Table 1 Specific surface area of ​​different lithium iron phosphate powder samples

[0031] A B C <![CDATA[Specific surface area (m 2 / g)]]> 12.14 12.11 12.15

[0032] The particle size of these three lithium iron phosphates was measured using a Mastersizer 3000 laser particle size analyzer. The results are as follows:

[0033] Table 2 Particle size of different lithium iron phosphate powder samples

[0034]

[0035] It can be seen from the results in Tables 1 and 2 that the specific surface areas and particle sizes of the three lithium iron phosphate samples are similar, and the carbon coating situation cannot be described.

[0036] 1. Heat the three lithium iron phosphate powder samples A, B, and C in air atmosphere at a heating rate of 5-15°C / min to 500°C using a Shimadzu DTG-60 thermogravimetric-differential thermal instrument (such as Figure 1The extrapolated starting temperature, extrapolated end temperature and mass increase ratio of the sample are analyzed and determined as shown in the figure. The specific operation method is as follows: two alumina crucibles of exactly the same mass and size are placed at both ends of the balance of the thermogravimetric-differential thermal instrument, the balance is zeroed, and the reading is stabilized; 5-15 mg of lithium iron phosphate powder sample without large particle agglomeration is evenly filled into one of the alumina crucibles, and the reference material is filled into the other alumina crucible; the DTA signal is adjusted to return the differential thermal reading to zero; the sample in the crucible is heated to no more than 500°C, and the TG-DTA curve is analyzed according to the test data to obtain the extrapolated starting temperature, extrapolated end temperature and mass increase ratio of the sample.

[0037] 2. Compare the extrapolated starting temperature and end temperature of the oxidation of divalent iron to trivalent iron of different lithium iron phosphate powder samples, that is, the starting temperature and ending temperature of lithium iron phosphate oxidation; at the same time, compare the degree of mass change of these three lithium iron phosphate powder samples, that is, the mass increase ratio.

[0038] The differential thermal analysis of three lithium iron phosphate powder samples A, B, and C heated to 500°C in air atmosphere is shown in the following figure: Figure 2 As shown in the thermogravimetric analysis diagram, Figure 3 shown.

[0039] Table 3 Extrapolated starting point temperature, extrapolated end point temperature and mass increase ratio of different lithium iron phosphate powder samples

[0040] A B C Extrapolation starting point / ℃ 370.01 382.12 388.65 Extrapolated endpoint / ℃ 427.05 435.03 438.99 Mass increase ratio 2.468% 2.095% 1.576%

[0041] From the data in Table 3, it can be seen that the extrapolated starting point temperature and the extrapolated end point temperature of samples A, B, and C are C>B>A, and the actual carbon coating degree is: C>B>A, and its trend is consistent with the actual result. And the mass increase ratio is A>B>C, indicating that the proportion of uncoated lithium iron phosphate in A is the largest and the uniformity is the worst, which is consistent with the actual carbon coating degree.

[0042] The oxidation decomposition temperature of lithium iron phosphate is also related to the particle size and specific surface of lithium iron phosphate. The results in Tables 1-3 show that the different oxidation temperatures of lithium iron phosphate are caused by different carbon coatings.

[0043] Embodiment 2: The rest is the same as Embodiment 1, except that:

[0044] The three types of lithium iron phosphate A, B, and C were heated to 500°C in a nitrogen atmosphere and analyzed using a Shimadzu DTG-60 thermogravimetric-differential thermal instrument. The differential thermal analysis results are shown in Figure 4 As shown in the thermogravimetric analysis, Figure 5 shown.

[0045] Depend on Figure 4 and Figure 5 It is known that in Figure 2 and Figure 3 The change of the curve at around 400°C is due to the oxidation reaction of lithium iron phosphate. At this position, the Fe 2+ Oxidized to Fe 3+ , as lithium iron phosphate reacts with oxygen, the mass of the sample increases.

[0046] Embodiment 3: The rest is the same as Embodiment 1, except that:

[0047] The carbon source of lithium iron phosphate (ie, conductive carbon) was heated to 800°C in an air atmosphere and analyzed using a Shimadzu DTG-60 thermogravimetric-differential thermal instrument. The analysis results are as follows: Figure 6 shown.

[0048] In this embodiment, the extrapolated starting point temperature of the reaction between the carbon source of lithium iron phosphate and oxygen is 704.70°C, and the extrapolated end point temperature is 786.35°C. At 400°C, the carbon source does not participate in the oxidation reaction. Figure 2 and Figure 3 The changes occurring at 400°C are caused only by the reaction of incompletely coated lithium iron phosphate with oxygen in the air and have nothing to do with the carbon coating.

[0049] Embodiment 4: All other aspects are the same as Embodiment 1, except that:

[0050] The carbon source of lithium iron phosphate (ie, conductive carbon) was heated to 800°C in a nitrogen atmosphere and analyzed using a Shimadzu DTG-60 thermogravimetric-differential thermal instrument. The analysis results are as follows: Figure 7 shown.

[0051] Figure 7 show Figure 6 The DTA peak at 600-800 °C is produced by the oxidation reaction between the carbon source and oxygen.

[0052] Figure 2-7 It shows that the carbon coating uniformity of the sample is positively correlated with the extrapolated starting temperature and the extrapolated end temperature at 500°C, but negatively correlated with the mass increase ratio.

[0053] Embodiment 5: All other aspects are the same as Embodiment 1, except that:

[0054] Sample A was replaced with standard lithium iron phosphate powder material D with a carbon coating of 99.26%; sample C was replaced with standard lithium iron phosphate powder material F with a carbon coating of 99.74%, and the sample to be tested was sample E with an unknown carbon coating. There was no difference in the particle size and specific surface area of ​​standard D, sample E, and standard F.

[0055] After testing, the extrapolated starting point temperature, extrapolated end point temperature and mass increase ratio of standard D, sample E and standard F are as follows:

[0056] Table 4 Extrapolated starting point temperature, extrapolated end point temperature and mass increase ratio of standards and samples

[0057] D E F Extrapolation starting point / ℃ 372.16 379.27 393.44 Extrapolated endpoint / ℃ 430.11 434.05 441.52 Mass increase ratio 2.331% 2.174% 1.332%

[0058] From the results in Table 4, it can be seen that the coverage of sample E is between 99.26% and 99.74%.

Claims

1. A method for detecting the uniformity of carbon coating of lithium iron phosphate powder material, characterized in that: The steps include: The lithium iron phosphate powder material is used as a sample and heated in an oxygen atmosphere, and the extrapolated starting temperature, extrapolated end temperature and mass increase ratio of the sample are respectively measured. The uniformity of the carbon coating of the lithium iron phosphate powder material is judged according to the relative sizes of the extrapolated starting temperature, extrapolated end temperature and mass increase ratio of different samples.

2. The method for detecting the uniformity of carbon coating of lithium iron phosphate powder material according to claim 1, characterized in that: The oxygen atmosphere is an air atmosphere, and the heating temperature is no more than 500°C.

3. The method for detecting the uniformity of carbon coating of lithium iron phosphate powder material according to claim 1, characterized in that: The heating temperature is 300-500°C.

4. The method for detecting the uniformity of carbon coating of lithium iron phosphate powder material according to claim 1, characterized in that: The sample includes at least one lithium iron phosphate powder material standard with a known carbon coating degree and at least one lithium iron phosphate powder material to be tested with an unknown carbon coating degree.

5. The method for detecting the carbon coating uniformity of lithium iron phosphate powder material according to claim 1, characterized in that: The method for determining the extrapolated starting point temperature, the extrapolated end point temperature and the mass increase ratio of the sample is as follows: placing two completely identical crucibles at both ends of a balance of a thermogravimetric-differential thermal instrument, returning the balance to zero, and waiting for the indication to stabilize; evenly filling the sample into one of the crucibles, and filling the reference material into the other crucible; adjusting the DTA signal, and returning the differential thermal indication to zero; heating the sample in the crucible to no more than 500° C., analyzing the TG-DTA curve according to the test data, and obtaining the extrapolated starting point temperature, the extrapolated end point temperature and the mass increase ratio of the sample.

6. The method for detecting the carbon coating uniformity of lithium iron phosphate powder material according to claim 5, characterized in that: The method for heating the sample in the crucible is: heating to 500° C. at a heating rate of 5-15° C. / min.

7. The method for detecting the carbon coating uniformity of lithium iron phosphate powder material according to claim 5, characterized in that: The method for evenly filling the sample into the crucible is: evenly filling 5-15 mg of lithium iron phosphate powder sample without large particle agglomeration into the alumina crucible.

8. The method for detecting the carbon coating uniformity of lithium iron phosphate powder material according to claim 1, characterized in that: The method for judging the uniformity of carbon coating of lithium iron phosphate powder material according to the relative sizes of the extrapolated starting temperature, extrapolated endpoint temperature and mass increase ratio of different samples is as follows: the extrapolated starting temperature, extrapolated endpoint temperature and mass increase ratio of different samples are compared respectively. The samples with relatively higher extrapolated starting temperature and extrapolated endpoint temperature and relatively smaller mass increase ratio have higher carbon coating uniformity.